Development and in-depth investigation of pre-service teachers' digital competencies based on DigCompEdu: a case study - Haşlaman, Tülin; Atman Uslu, Nilüfer; Mumcu, Filiz (Quality & quantity, 2024)
The purpose of this study is twofold: (a) To develop digital competencies of pre-service teachers in an educational process; (b) To describing their digital competences by examining artefacts designed by pre-service teachers based on DigCompEdu framework. Holistic single case study was employed in this study and the course was examined as a single unit. The study group consisted of 40 pre-service teachers. A 14-week course has been designed to develop the digital competencies of pre-service teachers based on the DigCompEdu framework. The e-portfolios and reflection reports of 40 pre-service teachers who participated in the study were examined and evaluated according to the indicators presented for each competence within the framework of DigCompEdu. Pre-service teachers' digital competences were assessed as folows: mostly C2 level in digital resources; mostly C1 level in teaching and learning, and mostly B2 level in assessment and empowering learning. An education process that blends theoretical and practical assignments for the pre-service teachers' digital competencies to be improved was conducted in this study. It is expected that the steps that were followed in the study in the process of training pre-service teachers be directive towards researchers who wish to study this subject. It is important that contextual and cultural qualities are taken into consideration in the interpretation of the findings in the study. This study contributes to the literature in terms of evaluating the digital skills of pre-service teachers based on reflection reports and e-portfolios, instead of self-report surveys.